(untitled) (Indian Journal of Public Health Research & Development, 2020)
Diarrhea is one of the most common manifestations of illness in infants and children. Diarrhea is a symptom of variety of conditions, and it constitutes one of the main causes of morbidity and mortality among infants and throughout the world1. The resent study was to assess the level of knowledge on home management of diarrhea among the mothers”and the objectives were to assess the existing level of knowledge on home management of diarrhea among mothers and to associate the level of knowledge on home management of diarrhea with their selected demographic variables. Non experimental –descriptive research study was conducted. The study sample consisted of total 100 mothers of under five children. The study finding shows that majority of the mothers were having inadequate knowledge and most of the mothers were having moderate knowledge and no mother were having adequate knowledge. The mean value of knowledge score was 9 and the standard deviation was 3. The study findings also shows that there is no significant association between the demographic variables such as (age, education, income, type of family, residence, source of information) and the level of knowledge of mothers regarding home management of diarrhea at p<0.05 level.